Magnetic, Electrical Conductivity, and EPR Investigations of a Low-Spind5System in Fe8V10W16O85 - Guskos, N.; V. Likodimos; Patapis, S.K.; Typek, J.; Wabia, M.; Fuks, H.; Gamari-Seale, H.; Walczak, J.; Rychlowska-Himmel, I.; Bosacka, M. (Journal of Solid State Chemistry, 1998)
The temperature dependence of the magnetic, electrical conductivity, and electron paramagnetic resonance (EPR) properties of Fe8V10W16O85has been investigated. The magnetic susceptibility measurements revealed an almost Curie-Weiss law behavior above room temperature and an additional magnetic interaction at low temperature, causing a steep rise of magnetization as the liquid helium temperature was approached. The value of the magnetic moment at high temperature,μeff=1.80μB, suggests a predominance of trivalent iron ions in a low-spin state. In the 300-4.2 K temperature range a difference between the zero field cooling (ZFC) and the field cooling (FC) modes was recorded. This irreversible behavior might be related to the presence of weakly coupled clusters. The EPR measurements revealed a broad, temperature-dependent resonance line at high temperature and two weaker lines at low temperature. The two low-temperature lines were attributed to antiferromagnetically coupled high-spin Fe3+ion clusters and to high-spin iron ions placed at sites with low symmetry of the crystal field. The broad line at high temperature was separated into two Lorentzian lines. These component lines were attributed to the two paramagnetic centers connected with the Fe3+ions involved in the magnetic structure of Fe8V10W16O85: dominant low-spin centers and a small admixture (<15%) of the high-spin centers. The line broadening and shift of the resonance field of the two component lines with decreasing temperature were studied and analyzed using a model of the EPR lines of antiferromagnets. The temperature dependence of the electrical conductivity showed a typical semiconducting-type behavior with an activation energy of 0.40 eV. The hopping mechanism of small polarons was proposed to explain the transport properties of the sample. © 1998 Academic Press.